Dosage Strategy of Linezolid According to the Trough Concentration Target and Renal Function in Chinese Critically Ill Patients - Wu, Fan; Zhang, Xiao-Shan; Dai, Ying; Zhou, Zi-Ye; Zhang, Chun-Hong; Han, Lu; Xu, Fang-Min; Wang, Ye-Xuan; Shi, Da-Wei; Lin, Guan-Yang; Yu, Xu-Ben; Chen, Fang (Frontiers in Pharmacology, 2022)
Background: Linezolid is associated with myelosuppression, which may cause failure in optimally treating bacterial infections. The study aimed to define the pharmacokinetic/toxicodynamic (PK/TD) threshold for critically ill patients and to identify a dosing strategy for critically ill patients with renal insufficiency. Methods: The population pharmacokinetic (PK) model was developed using the NONMEM program. Logistic regression modeling was conducted to determine the toxicodynamic (TD) threshold of linezolid-induced myelosuppression. The dosing regimen was optimized based on the Monte Carlo simulation of the final model. Results: PK analysis included 127 linezolid concentrations from 83 critically ill patients at a range of 0.25–21.61 mg/L. Creatinine clearance (CrCL) was identified as the only covariate of linezolid clearance that significantly explained interindividual variability. Thirty-four (40.97%) of the 83 patients developed linezolid-associated myelosuppression. Logistic regression analysis showed that the trough concentration (Cmin) was a significant predictor of myelosuppression in critically patients, and the threshold for Cmin in predicting myelosuppression with 50% probability was 7.8 mg/L. The Kaplan–Meier plot revealed that the overall median time from the initiation of therapy to the development of myelosuppression was 12 days. Monte Carlo simulation indicated an empirical dose reduction to 600 mg every 24 h was optimal to balance the safety and efficacy in critically ill patients with CrCL of 30–60 ml/min, 450 mg every 24 h was the alternative for patients with CrCL <30 ml/min, and 600 mg every 12 h was recommended for patients with CrCL ≥60 ml/min. Conclusion: Renal function plays a significant role in linezolid PKs for critically ill patients. A dose of 600 mg every 24 h was recommended for patients with CrCL <60 ml/min to minimize linezolid-induced myelosuppression.